Penyelesaian Tanah Sultan Ground dan Pakualaman Ground yang Dikuasai Masyarakat Berdasarkan Asas Kerakyatan - Parakleyto Majma Al-Bahrayn; Lego Karjoko; Rahayu Subekti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research discusses the settlement of Sultan Ground (SG) and Pakualaman Ground (PAG) land controlled by the community based on the principle of people's sovereignty. The special status of the Yogyakarta Special Region (DIY) grants the Sultanate and Pakualaman Duchy the authority to manage SG and PAG land. However, in practice, the inventory process of these lands has led to legal issues, particularly concerning ownership and the rights of communities that have long occupied the land. This study employs normative legal research methods with statutory and conceptual approaches. The sources of data include primary, secondary, and tertiary legal materials. The findings indicate a dualism in agrarian law between the Basic Agrarian Law (UUPA) and the Yogyakarta Special Region Law, which results in legal uncertainty for communities that have long inhabited SG and PAG land. The study concludes that the community's rights over SG and PAG land before the inventory process can be based on the magersari and anggaduh principles, which are recognized in customary law. However, the lack of legal recognition within the national legal system causes communities to lose rights over the land they have utilized for generations. Therefore, a legal solution that accommodates the principle of people's sovereignty is needed to resolve land disputes in Yogyakarta, ensuring legal certainty and justice for the community.